Emergence of artistic talent in progressive nonfluent aphasia: a case report. Issue 6 (19th February 2019) - Hamauchi, Akiko; Hidaka, Yosuke; Kitamura, Izumi; Yatabe, Yusuke; Hashimoto, Mamoru; Yonehara, Toshiro; Fukuhara, Ryuji; Ikeda, Manabu
Abstract : Some patients with frontotemporal lobar degeneration have developed artistic skills after the onset mainly in painting and music. Most of these cases have semantic dementia (SD), one of the frontotemporal lobar degeneration subtypes. In previously reported cases, the paintings made by patients with SD were usually hyper realistic, without a significant symbolic or abstract component. Here, we report on a patient with progressive nonfluent aphasia (PNFA), another frontotemporal lobar degeneration subtype, who started making creative bamboo crafts after PNFA onset. His techniques were completely his original; he devised the shapes of the crafts and made them without samples. His work did not become an obsessive preoccupation. The artistic style expressed by patients with PNFA differs from that expressed by patients with SD. Therefore, the underlying mechanisms for the emergence of artistic talent might differ between SD and PNFA.